Cover. (24th September 2018) - Lynch, Anne M.; Berning, Amber A.; Thevarajah, Tamara S.; Wagner, Brandie D.; Post, Miriam D.; McCourt, Emily A.; Cathcart, Jennifer N.; Hodges, Jennifer K.; Mandava, Naresh; Gibbs, Ronald S.; Palestine, Alan G.
Abstract : The cover image, by Anne M. Lynch et al., is based on the Original Article The role of the maternal and fetal inflammatory response in retinopathy of prematurity, DOI:10.1111/aji.12986 .